SaaS quality of service attributes - Khanjani, Atieh; Wan Ab. Rahman, Wan Nurhayati; Abd Ghani, Abdul Azim; Md Sultan, Abu Bakar (Asian Network for Scientific Information, 2014)
Software as a Service (SaaS) is one of the cloud computing branch and it is rapidly growing. Quality of Service (QoS) for SaaS cloud is considered as an important concern among researchers. The QoS specification, particularly, for SaaS is known as a big gap in current researches. Therefore, in this study, the main QoS attributes for SaaS consisting of 33 attributes have been reviewed. The results show a comprehensive specification of QoS attributes for SaaS which cover more aspects of QoS for SaaS excluding the business perspective. The attributes then have been classified in terms of both user and provider perspectives and can be useful as a guideline for both users and providers.